2016
DOI: 10.1016/j.amepre.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Dental Homes for Children With Autism

Abstract: Introduction Medicaid-enrolled children with autism spectrum disorder (ASD) encounter significant barriers to dental care. Iowa’s I-Smile Program was implemented in 2006 to improve dental use for all children in Medicaid. This study compared dental home and preventive dental utilization rates for Medicaid-enrolled children by ASD status and within three time periods (pre-implementation, initial implementation, maturation) and determined I-Smile’s longitudinal influence on ASD-related dental use disparities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…SHCN has been classified as a moderate risk for dental caries in children at 0–5 years ( 37 ). Chi and colleagues found that children with autism were less likely to utilize preventive dental care than those without autism ( 38 ). All those findings indicated that children with complex medical conditions tend to have more dental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…SHCN has been classified as a moderate risk for dental caries in children at 0–5 years ( 37 ). Chi and colleagues found that children with autism were less likely to utilize preventive dental care than those without autism ( 38 ). All those findings indicated that children with complex medical conditions tend to have more dental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased reimbursement also increased utilization of preventive services in dental offices, but it created gaps and exacerbated disparities for certain groups requiring comprehensive care (5)(6)(7)(8). For example, children with autism or intellectual and developmental disability had lower preventive care utilization than their peers (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of children who required assistance from an adult to perform tooth brushing and did not do so independently ranged from 64.2% (Hage et al, 2020) to 68.0% (Orellana et al, 2019). Medicaid-enrolled children aged 3–17 years with ASD were significantly less likely to utilize preventive care than children without ASD (Chi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of children who required assistance from an adult to perform tooth brushing and did not do so independently ranged from 64.2% (Hage et al, 2020) to 68.0% (Orellana et al, 2019). Medicaid-enrolled children aged 3-17 years with ASD were significantly less likely to utilize preventive care than children without ASD (Chi et al, 2016). Murshid (2015) found that half of the healthcare providers did not provide guidance regarding the importance of oral hygiene and how to perform it on their children.…”
Section: Oral Health Practices Among People With Asd Caregiversmentioning
confidence: 99%